A gender perspective on perceived causes of sick leave due to common mental disorders among young Swedish employees: A qualitative interview study. - Caroline Olsson; Helena Tinnerholm Ljungberg; Elisabeth Björk Brämberg; Lotta Nybergh; Irene Jensen (PLoS ONE, 2023)
Objective Common mental disorder (CMD) is the most common reason for sick leave among young employees in Sweden, with young women having a higher prevalence. There is a lack of studies focusing on young employees' own perceptions of sick leave. The aim was twofold: to investigate 1) perceived causes of sick leave due to CMD among young employees, and 2) differences and similarities among women and men. Methods Using a qualitative design with an applied gender perspective enabled us to capture young employees' gendered experiences and consider cultural and social aspects of their situations. We interviewed 13 women and 12 men (aged 20-29) with experience of being on sick leave and applied a conventional inductive content analysis. Results Six categories were identified: a) Being new to the labour market and the workplace; b) Want to prove themselves; c) To be exposed to poor working conditions; d) Relations at work; e) Being vulnerable; and f) Additional private life burdens. Conclusion This study adds to the understanding of young employees' perceived causes of sick leave due to CMD, by letting them share their experiences of events prior to sick leave connected to work and private life. Similarities and differences in women's and men's experiences were revealed. Overall, both young men and women describe a more pressured work situation for young women compared to their male counterparts, that young women take more social responsibility in private life and at work whereas men on the other hand find it harder to disclose mental health problems.